Resiliensi Akademik terhadap Santri yang Memiliki Tiga Peran - Luthfiyah, Malika; Kutub Hardew, Ayatullah (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
One of the Islamic Boarding Schools located in Bekasi, West Java has a special program that applies to the students, specifically the third level of Aliyah students. The program is in the form of lecture activities that must be followed to meet the graduation requirements for final-year students so that students have three roles. First, the students play the role of third-grade student Aliyah. Second, students play the role of freshmen. Third, the student acts as a student. The three roles of Aliyah third-level students require academic resilience that can help them face difficulties and problems during the learning process. This research uses qualitative methods with a phenomenological approach. The data collection method used semi-structured interview methods and non-participant observation, as well as documentation studies. Furthermore, data analysis uses interpretative phenomenological analysis (IPA) with atlas. ti software. This study aims to find out how the picture of academic resilience in students who have three roles. The result of this study is that the academic resilience of students is built by the ability of students to regulate emotions, control impulses, be optimistic, conduct environmental and condition analysis, self-efficacy, and reaching out. Keywords: